Patterns of island change and persistence offer alternate adaptation pathways for atoll nations - Paul S. Kench; Murray R. Ford; Susan D. Owen (Nature Communications, 2018)
Inundation and erosion could make many atoll islands uninhabitable over the next century. Here the authors present an analysis of change in the atoll nation of Tuvalu that shows a 2.9% increase in land area over the past four decades, with 74% of islands increasing in size, despite rising sea levels.